A series of photochemical based studies into the application of green chemistry principles to potentially industrially relevant chemical reactions - Hunter, Jonathan (2021)
This Thesis details several research areas which attempt to address some of the issues associated with industrial scale photochemical reactions. In the first Chapter, an overview of industrial scale photochemistry is given, and these approaches have been critiqued from a green chemistry perspective. From this introduction, three main aims of the Thesis have been developed and are explored in the subsequent chapters. These are 1) to explore routes in improve the “green credentials” of a photoredox reaction, specifically for amide bond synthesis; 2) to develop a reactor which was capable of safely conducting photochlorination and use this system to try to solve several long-standing issues with this reaction; 3) to study the application of bio-derived solvents for use in photochemical reactions. The efforts towards achieving these aims resulted in varying levels of success.